Investigating the firing protocol of Athenian pottery production: A Raman study of replicate and ancient sherds. (25th February 2015) - Cianchetta, Ilaria; Maish, Jeff; Saunders, David; Walton, Marc; Mehta, Apurva; Foran, Brendan; Trentelman, Karen; Marshall, Craig P.
<x xml:space="preserve">Abstract</x> The black and red coloration of ancient Athenian pottery is due to the different oxidation states of iron oxide: reduced Fe2+ (black) and oxidized Fe3+ (red). It has long been thought that a single, three‐step firing — oxidation–reduction–oxidation — was used to manipulate the Fe valence state and achieve different degrees of vitrification between the slip and the body to produce the high contrast black and red images. However, complex and layered structures, with slips of different color overlaying each other, are sometimes found, raising the question of the adequacy of a single three‐step firing to produce complex architectures. The firing conditions used in the production of an ancient vessel in the collection of the J. Paul Getty Museum, in which a red glossy layer is found between the black gloss and the body, were investigated. The ancient specimen was compared to a set of replicates produced and fired under a series of controlled temperatures and oxygen fugacities. Raman spectroscopy was used to identify the mineralogical phases present in both the ancient and the replicate samples, and the shape and position of the Eg mode in hematite provided a measure of the temperatures at which the minerals were formed. The results suggest the ancient vessel was produced using at least two separate firings: a high temperature firing under oxidizing conditions to create the underlying red glossy layer, followed by a three‐step firing to create the surface black gloss decoration. This finding suggests the firing of ancient Athenian pottery was more complex than previously thought. Copyright © 2015 John Wiley & Sons, Ltd.